On the origin of chloroplasts, import mechanisms of chloroplast-targeted proteins, and loss of photosynthetic ability - review - Vesteg, M; Vacula, R; Krajcovic, J (Folia microbiologica, 2009)
Primary plastids of green algae (including land plants), red algae and glaucophytes are bounded by two membranes and are thought to be derived from a single primary endosymbiosis of a cyanobacterium in a eukaryotic host. Complex plastids of euglenids and chlorarachneans bounded by three and four membranes, respectively, most likely arose via two separate secondary endosymbioses of a green alga in a eukaryotic host. Secondary plastids of cryptophyta, haptophyta, heterokontophyta and apicomplexan parasites bounded by four membranes, and plastids of dinoflagellates bounded by three membranes could have arisen via a single secondary endosymbiosis of a red alga in a eukaryotic host (chromalveolate hypothesis). However, the scenario of separate tertiary origins (symbioses of an alga possessing secondary plastids in a eukaryotic host) of some (or even most) chromalveolate plastids can be also consistent with the current data. The protein import into complex plastids differs from the import into primary plastids, as complex plastids contain one or two extra membrane(s). In organisms with primary plastids, plastid-targeted proteins contain N-terminal transit peptide which ferries proteins through the protein import machineries (multiprotein complexes) of the two (originally cyanobacterial) membranes. In organisms with complex plastids, the secretory signal sequence directing proteins to endomembrane system and afterwards through extra outermost membrane(s) is generally present upstream of the classical transit peptide. Several free-living as well as parasitic eukaryotes possess non-photosynthetic plastids. These plastids have generally retained the plastid genome, functional plastid transcriptional and translational apparatus, and various metabolic pathways, suggesting that though these plastids lost their photosynthetic ability, they are essential for the mentioned organisms. Nevertheless, some eukaryotes could have lost chloroplast compartment completely.
Keywords: plastidy; Photosynthesis; transport proteinů; Eukaryota; proteiny; Protein Transport; Proteins; Chloroplasts; biologická evoluce; Biological Evolution; fotosyntéza; Plastids; chloroplasty